Out of our minds : reason and madness in the exploration of Central Africa : the Ad. E. Jensen lectures at the Frobenius Institut, University of Frankfurt - Fabian, Johannes (University of California Press, 2000)
'Out of Our Minds' shows explorers and ethnographers in Africa during colonial expansion were far from rational - often meeting their hosts in extraordinary states influenced by opiates, alcohol, sex, fever, fatigue, and violence.